Redistribution of Income through Social Benefits over the Life Course in the Baltic States - Skuciene, Daiva; Lazutka, Romas (Studies of Transition States and Societies, 2019)
Vertical redistribution refers to the transfer of income from those who have more than they need to those who are in need and is related to the levelling of income inequality and poverty. Vertical redistribution over the life course is indicative of the capacity of the welfare state to protect against social risks over the life course. Studies that explore such redistribution often rely on the life-course perspective and use secondary cross-sectional rather than primary data. The goal of the current study is to analyse the impact of social benefits on income inequality and poverty over the life course in the Baltic States. The paper focuses on the three Baltic countries commonly characterised by successful economic performance, low income redistribution and high income inequality. With this aim, analyses of micro-level data of EU-SILC of 2015 was conducted. To evaluate inequality changes across the life course, the study used a decomposition of the Gini index. Evaluation of poverty of different cohorts rested on the gap of the poverty rate between different groups and the average poverty rate in the country. The findings of our study suggest that the impact of social benefits on the reduction of income inequality is modest. Highest poverty rates are linked with the periods of childhood, working age when unemployed and old age. Overall, the context laden with high inequality and poverty cannot ensure adequate protection against social risks over the life course and create a “buffer” for the development of human capital.